Paw preference in wolves (Canis lupus): A preliminary study using manipulative tasks. Issue 1 (4th March 2021) - Regaiolli, Barbara; Mancini, Luca; Vallortigara, Giorgio; Spiezio, Caterina
ABSTRACT: Behavioural and brain lateralization is widespread among non-human vertebrates. Motor lateralization has been investigated in the domestic dog, revealing that "pawedness" in this species seems to be sex and task related; however, few if any studies considered this asymmetry in wolves ( Canis lupus ). The aim of this study was to investigate the paw preference of seven wolves housed at Parco Natura Viva – Italy, during the interaction with food-related (FD) and olfactory (OLF) environmental enrichment devices. Eleven sessions were done (22 session in total) per condition (FD and OLF), and data about enrichment manipulation were collected. Most of the wolves manipulated the enrichment devices using one paw rather than both paws. At the individual level, all subjects were lateralized in paw use, six were right pawed, one was left pawed (the alpha male) regardless of the enrichment condition. The fact that one paw rather than both was frequently involved in manipulation could indicate a practical advantage for each individual in being lateralized in paw use. Despite the small sample size, our results provide interesting insights about lateralization in wolves, deserving further investigations. More studies are needed considering factors such as temperament, social rank and task complexity on canid motor lateralization.